Exploring the impact process and mechanism of geological hazards on land use from the perspective of debris flow gullies - Liu, Xiaobo; Zhu, Ran; Zhang, Hao; Zhuo, Xiaoshuang (Frontiers in Earth Science, 2025)
Geological disasters like debris flows often profoundly affect land use, causing changes in the surrounding environment and influencing the decisions of local farmers. This study selected 122 debris flow gullies in the Anning River Basin as research units and developed a novel analytical approach to quantify land use responses to debris flows. Key indicators derived from this methodology were combined with ordinary least squares (OLS) regression analysis to identify critical factors governing the spatial distribution patterns of land use. Building on these analyses, the research further elucidated the mutual interaction mechanisms between debris flow disasters and land use dynamics. The findings indicate that 1) the cultivated land and rural construction land are predominantly concentrated in the piedmont areas, accounting for 50.74% and 60.04% of the total area, respectively. 2) The land use concentration index values of the various land types are ranked in descending order as follows: water bodies, forested areas, barren land, agricultural land, grasslands, and built-up areas. 3) There is marked spatial clustering of the land use types in relation to the altitude, proximity to roads, and population distribution, with Moran’s I indices of 0.975, 0.957, and 0.949, respectively, indicating strong spatial autocorrelation. The impact of altitude on the distribution of the cultivated land is most pronounced in the gullies characterized by medium-frequency debris flows, and a significant proportion (50.00%) have positive regression coefficients. Conversely, the aspect exerts the most substantial positive influence on the cultivated land in the gullies with low debris flow frequencies, and the majority (59.09%) have positive regression coefficients. The results of this study underscore that the slope gradient and altitude are critical determinants of the spatial distribution of land use types within the debris flow gullies. The findings offer empirical evidence to support the development of land use policies that aim to reduce the risk of debris flow occurrences while promoting sustainable land management practices.